Transient Creatine Kinase Elevation Followed by Hypocomplementemia in a Case of Rotavirus Myositis. (13th March 2016) - Rokugo, Yuka; Kumaki, Satoru; Onuma, Ryoichi; Noguchi, Rie; Suzuki, Saeko; Kusaka, Natsuko; Watanabe, Yohei; Kitaoka, Setsuko
Abstract : We report an infant case of rotavirus myositis, a rare complication of rotavirus infection. Complement levels of the patient were normal when serum creatine kinase (CK) level was at its peak and then decreased when the CK level became normalized. In a previous case report of rotavirus myositis, transient decrease of serum albumin, immunoglobulin, and complement levels was reported. The authors speculated that intravascular complement activation was caused by rotavirus and resulted in the pathogenesis of myositis, although complement levels at onset were not measured by the authors. In this report, however, we demonstrate that the complement activation of our patient is a result of, rather than the cause of, skeletal muscle damage.